3D-scaffold design of biodegradable nanofibers for tissue regeneration and drug delivery - Wan Abdul Khodir, Wan Khartini; Yusof, Mohd Reusmaazran (Bentham Science Publishers, 2024)
Materials with specific properties and structures are required for 3D nanofibers scaffold to perform well during tissue regeneration and drug delivery applications. When designing and fabricating 3D scaffolds, it is crucial to consider how the biomaterials interact with the native tissue structures and how they function in the surrounding environment. This chapter provided a brief discussion on the fabrication methods used to construct 3D biodegradable polymeric nanofibers scaffolds through electrospinning from 2D structures. Further, it extended to the characterisation required for the scaffold to be used in either tissue engineering or drug delivery. Additionally, this chapter presented recent progress in the practical application of 3D scaffolds that incorporate different therapeutic agents.